THE CORRELATION BETWEEN GRAMMAR MASTERY AND SPEAKING ABILITY OF THE EIGHTH GRADE STUDENTS - Veltiana Ilam; Luh Ketut Sri Widhiasih; Ni Made Wersi Murtini (Academic Journal on English Studies (AJOES), 2022)
The purpose of this study is to find out the correlation between grammar mastery and speaking ability. The subject of the study was the eighth grade students of SMP TP 45 Denpasar in academic year 2021/2022 with a total of 40 students. The design of this research is a correlation that includes quantitative research. There were two instruments to judge the students’ skills in students’ grammar mastery and students’ speaking ability. The instruments were constructed based on the criteria suggestions of the first and second advisors. There were two variables in this research, independent variable (X) and dependent variable (Y), where grammar mastery as (X) speaking ability as (Y) variable. Quantitative analysis was done using statistics which is called statistics analysis or inferential statistics on SPSS 24 Version. Based on the data analysis, it was figured out that there was a significant correlation between students’ grammar mastery and students’ speaking ability of the eighth grade students of SMP TP 45 Denpasar in academic year 2021/2022. Based on the result by using SPSS 24 Version from the table 4.5 the correlation for students’ grammar mastery and students’ speaking ability was 0.423. In addition, these two data were correlated with each other.